Isolation and characterization of bacterial isolates for bioremediation of disposed x-ray sheets to produce silver nanoparticles - Siti Hajar, Mohd Rasdi (2018)
The production of x-ray sheets can utilize up to 1000 tons of silver chemically produced worldwide. The pollution occurs when the used x-ray sheets are not recycled. Microbial management could be used to manage this problem in order to remove and neutralize the pollutants from contamination. This study aims to examine the microbial management of disposed x-ray sheets in silver nanoparticles (SNPs) production and the role of the nitrate reductase (NR) enzyme involved in the processes. In this research, disposed x-ray sheets were used as the sole carbon source to synthesis SNPs and catalyse the reduction of silver nitrate to silver nitrite. Different bacterial isolates which had been chosen from the most potent isolates were used and being optimized by using several parameters including incubation condition, substrate concentration, incubation period, pH values and nitrogen source. Then, the protein quantification and enzyme activity were analyzed by using microplate reader. For characterization of the SNPs, the X-Ray Diffraction (XRD) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) analysis were used. The results revealed that the most potent isolates CL4C and GL7 showed the average size of SNPs produced was up to 19.53 nm and 52.35 nm respectively. In addition, NR activity was found to be optimum at static incubation condition, 15 days incubation period in darkness and using sodium nitrate as the nitrogen source. Then, substrate concentration of CL4C and GL7 isolates found to be optimum when 0.5 and 0.8g of disposed x-ray sheets were added respectively. The optimum pH values of CL4C and GL7 were exhibited to be 7.0 and 8.0, respectively, with the enzyme activity and protein content up to 69.952±0.090 IU/ml and 1.139±0.029 mg/ml for CL4C. Meanwhile, the NR activity of the GL7 isolate was 108.882±0.354 IU/ml with the protein content up to 1.454±0.024 mg/ml. Consequently, the CL4C isolate was predicted to be Morganella morganii while GL7 was predicted to be Enterobacter aerogenes by using a Biolog analysis. It can be concluded that, by using the biological method, it requires less toxic chemicals and as a good alternative for bioremediation. In this study, the impact of having isolated CL4C and GL7 as the most potent microbe which able to use disposed x-ray sheets as substrate was a new finding in this research area because there was no previous study yet regarding the uses of this substrate.